Life expectancy among HIV-positive patients in Rwanda: a retrospective observational cohort study. Issue 3 (March 2015) - Nsanzimana, Sabin; Remera, Eric; Kanters, Steve; Chan, Keith; Forrest, Jamie I; Ford, Nathan; Condo, Jeanine; Binagwaho, Agnes; Mills, Edward J
Summary Background Rwanda has achieved substantial progress in scaling up of antiretroviral therapy. We aimed to assess the effect of increased access to antiretroviral therapy on life expectancy among HIV-positive patients in two distinct periods of lower and higher antiretroviral therapy coverage (1997–2007 and 2008–11). Methods In a retrospective observational cohort study, we collected clinical and demographic data for all HIV-positive patients enrolled in care at 110 health facilities across all five provinces of Rwanda. We included patients aged 15 years or older with a known enrolment date between 1997 and 2014. We constructed abridged life tables from age-specific mortality rates and life expectancy stratified by sex, CD4 cell count, and WHO disease stage at enrolment in care and initiation of antiretroviral therapy. Findings We included 72 061 patients in this study, contributing 213 983 person-years of follow-up. The crude mortality rate was 33·4 deaths per 1000 person-years (95% CI 32·7–34·2). Life expectancy for the overall cohort was 25·6 additional years (95% CI 25·1–26·1) at 20 years of age and 23·3 additional years (95% CI 22·9–23·7) at 35 years of age. Life expectancy at 20 years of age in the period of 1997–2007 was 20·4 additional years (95% CI 19·5–21·3); for the period of 2008–11, life expectancy had increased to 25·6 additional years (95% CI 24·8–26·4). Individuals enrolling in care with CD4 cell counts of 500 cells per μL or more, and with WHO disease stage I, had the highest life expectancies. Interpretation This study adds to the growing body of evidence showing the benefit to HIV-positive patients of early enrolment in care and initiation of antiretroviral therapy. Funding Bill & Melinda Gates Foundation.